Changes in cannabis policy and prevalence of recreational cannabis use among adolescents and young adults in Europe—An interrupted time-series analysis - Alexander Carl Gabri; Maria Rosaria Galanti; Nicola Orsini; Cecilia Magnusson (PLoS ONE, 2022)
Background Cannabis policy varies greatly across European countries, but evidence of how such policy impacts on recreational cannabis use among young people is conflicting. This study aimed to clarify this association by investigating how changes in cannabis legislation influenced cannabis use. Methods Available data on self-reports of recreational cannabis use among individuals aged 15–34 years was retrieved from EMCDDA. Information on cannabis policy changes was categorized as more lenient (decriminalisation or depenalisation) or stricter (criminalisation, penalisation). Countries that had implemented changes in cannabis legislation or had information on prevalence of use for at least eight calendar years, were eligible for inclusion. We used interrupted time-series linear models to investigate changes in country-specific trajectories of prevalence over calendar time and in relation to policy changes. Results Data from Belgium, Czech Republic, Germany, Italy, Netherlands, Norway, Portugal, Slovakia, Spain, Sweden and United Kingdom, for 1994–2017 was available for analyses. Cannabis use varied considerably over the study period and between countries. On average, use was stable or weakly increasing in countries where legislation was not changed or changed at the extremes of the study period (+0.08 percent per year [95% CI -0.01, 0.17 percent]). In contrast, the pooled average use decreased after changes in legislation, regardless of whether it had become more lenient (-0.22 [-1.21, 0.77]) or stricter (-0.44 [-0.91, 0.03]). Conclusions Our findings do not support any considerable impact of cannabis legislation on the prevalence of recreational cannabis use among youth and young adults in Europe.